Biliary mucinous cystic neoplasm mimicking a hydatid cyst: a case report and literature review - Côme Tholomier; Yifan Wang; Olga Aleynikova; Tsafrir Vanounou; Jean-Sebastien Pelletier (BMC Gastroenterology, 2019)
Abstract Background Biliary mucinous cystic neoplasms are rare cystic lesions of the liver which carry pre-malignant potential. Given the scarcity of reports in the literature, they pose a considerable challenge to clinical management, particularly with regards to accurate pre-operative diagnosis. Case presentation We present the case of a 37-year-old Tunisian woman who presented with subacute right upper quadrant pain and a large multi-loculated cystic lesion, most consistent with a hydatid cyst. She underwent an open right hepatectomy, and pathology surprisingly revealed a biliary mucinous cystadenoma. Herein, we review the current literature on biliary mucinous cystic neoplasms, with a particular emphasis on diagnostic investigations, key radiological features and optimal treatment modalities. Conclusion Biliary mucinous cystic neoplasms require a high index of suspicion and should be managed with complete surgical resection, as conservative techniques are associated with high recurrence rates. Considering the potential for malignant transformation, periodical surveillance imaging is recommended in the post-operative period.